Disclosure of firms’ environmental performance - Hising, Jannike (2016)
Sustainability assessment of corporates has been recognized as an important and powerful tool to support a shift towards a sustainable development. In order to regulate activities with negative externalities and make socially responsible investment decisions, information and methods provided by third parties have become key instruments for investors and policy makers to mitigate market failures. However, assessment tools vary largely and despite being carefully developed, may not provide sustainable outcomes according to economic theories. Therefore, this present paper explores and critically examines the Sustainable Value (SV) approach developed by Figge and Hahn (2004) to measure corporate sustainable performance, focusing on the environmental indicator carbon dioxide emission.